The Swiss family Robinson - Wyss, Johann David 1743-1818 (Dover juvenile classics, 2001)
When a Swiss couple and their four sons are shipwrecked on an isolated island, they adapt to their "New Switzerland" using many imaginative methods of farming and animal taming.